Android-based Music Practice Material Complection Application - Rully Aprilia Zandra (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2018)
Millennials and Z-generation were born in the modern era. Since their birth, they have been surrounded by sophisticated technology. This generation always gets information quickly and limitless. They are very familiar with the internet and applications on smartphones. The most familiar application is generally based on Android. Android must also be used in the world of education. Android applications can be realized as a tool to deliver learning or supervision of learning. Supervision of learning in this development is limited to material comptetion. This development was developed from a paper-based initial device. The device focuses on students' practical skills in music. For this purpose, peer tutoring forms in drill supervision are very necessary. This study used a Research and Development method modified from Borg and Gall in 10 steps. The steps used are research and information collecting, planning, develop preliminary form of product, preliminary field testing, main product revision, main field testing, operational product revision, operational field testing, final product revision, dissemination and implementation. The first score validation were 65,25% from the IT validator, 70,50% from the media validator, and 75,25% from the material validator. The mean values in the small group trials were 70.50 and 78.25 in the large group trials. The final score from validation were 92,50% form the IT validation, 77,25% from the media validator, and 84,75% from the material validator. There are three applications that must be developed as recommendations from the results of this research. These three applications are: main teacher applications, admin applications, and student applications. Each application must be connected and updated in real-time.